Poverty, gender and reproductive justice. A qualitative study among adolescent girls in Western Uganda - Ninsiima, Anna B.; Michielsen, Kristien; Kemigisha, Elizabeth; Nyakato, Viola N.; Leye, Els; Coene, Gily (Health & Sexuality, 2020)
Low socio-economic status has been consistently identified as a primary risk factor for sexual and reproductive health violations affecting young women. This study shows how poverty interacts with gender power relations to impact upon adolescent girls’ sexual and reproductive lives in Western Uganda. Qualitative research with 147 participants was undertaken. This comprised 59 in-depth interviews and 11 focus group discussions with groups of 12–14 year-old young women, teachers and parents. Data were analysed manually using open and axial coding, and conclusions were generated inductively. Findings reveal that young women are restricted in exercising their sexual and reproductive rights not only by poverty and unequal gender relations, but also by corruption and poor service provision. In contrast to interventions using liberal rights-based approaches, we advocate the use of a ‘marketplace of options’ since access to sexual and reproductive health services is very limited for poor girls and not evenly distributed. Moreover, while poverty and unequal gender relations render girls vulnerable to sexual coercion and violence, the criminal justice system is often weak, leaving victims powerless. Investment in appropriate resources and inclusive and affordable access to justice is essential to advance young women’s sexual and reproductive health.
Keywords: Poverty; sexual and reproductive justic; gender; adolescents